Depression and affecting factors in patients over 50 years of age: A cross-sectional study - Mete, Burak; Fırıncı, Betül; Doğan, Esra; Pehlivan, Erkan (Journal of Surgery and Medicine, 2019)
Aim: The population of the elderly in the society is increasing. Old age problems and depression are over looked for various reasons. The aim of this study is to determine the level of life satisfaction of the demographically elderly living in the city or village/town and employing in work life, to determine the frequency of depression among these persons and to find the factors that may be related. Methods: 908 individuals over the age of 50 have been reached. Type of study is cross-sectional. Sociodemographic questionnaire, Euromodule questionnaire and Geriatric Depression Scale were administered to the subjects. Mann Whitney U, Kruskal Wallis test and Spearman correlation analysis, Binary Logistic regression analysis, Chi-square test were used in the analysis of the data. Results: The prevalence of depression was found to be 40% in people over 50 years of age. Being a woman, low income and education level, becoming a single/widow, to have a chronic illness and using regular medication increases the risk of depression(p <0.05). Having a hobby and a close friend, using social media decreased the risk of developing depression (p <0.05). Life satisfaction was found to be low-mid-level. Conclusion: Depression is common in people over 50 years of age. In terms of life satisfaction, urban and rural life seem to be superior to each other in some way.